Randomised clinical trial: sofosbuvir and ledipasvir in patients with transfusion‐dependent thalassaemia and HCV genotype 1 or 4 infection. Issue 4 (29th June 2017) - Mangia, A.; Sarli, R.; Gamberini, R.; Piga, A.; Cenderello, G.; Piazzolla, V.; Santoro, R.; Caruso, V.; Quarta, A.; Ganga, R.; Copetti, M.; Forni, G.
Summary: Background: Patients with thalassaemia major depend on blood transfusions. In Italy, up to 80% of thalassaemia patients bear HCV antibodies due to HCV contaminated transfusions before 1990. Thalassaemia patients with HCV infection have high risk of developing HCC. Treatment based on Pegylated‐IFN (Peg‐IFN) and Ribavirin (RBV) was limited by relevant side effects. Aim: To evaluate the impact of Sofosbuvir/Ledipasvir (SOF/LDV) fixed dose combination for 12 weeks without RBV, in patients with thalassaemia major and HCV Genotype 1 or 4 (GT1/4). Methods: Open label, historically‐controlled, nationwide multicentre study in thalassaemia patients including naïve with cirrhosis and prior treatment failure without cirrhosis. SOF/LDV single pill was administered for 12 weeks to 100 patients of whom 16% had cirrhosis. The control group included 96 patients with comparable baseline characteristics treated with Peg‐IFN/RBV. The primary end point was sustained virologic response at follow‐up week 12 or 24 after IFN‐free or Peg‐IFN/RBV, respectively. Results: In the study group, sustained virological response (SVR) was reported in 98% of patients (95% CI 95.3%‐100%). Cirrhotic as well as prior treatment failure achieved 100% SVR. In the control group, SVR was 47.9% (95% CI 37.9%‐57.9%). Adverse events including fatigue, headache, nausea, decrease in haemoglobin or increase in ferritin levels were rare and significantly less common in the study than in the historical control group. Conclusions: In conclusion, SOF/LDV for 12 weeks provides simple, highly effective and safe Peg‐IFN/RBV‐free treatment for HCV GT1/4 thalassaemia patients. EUDRACT number 2015‐002401‐1. Abstract : Linked Content This article is linked to Mangia et al and D'Ambrosio and Lampertico papers. To view these articles visithttps://doi.org/10.1111/apt.14251 andhttps://doi.org/10.1111/apt.14221 .